PREPARATION OF SUPERPARAMAGNETIC CALCIUM FERRITE NANOPARTICLES USING SOLID STATE TECHNIQUE AND ANALYSIS OF THEIR STRUCTURAL PROPERTIES - Robak Aziz Rashid; Dheyab T. Noori; Raham Z. Hadi (Antis-Publisher, 2026)
Objective: In the current experiment, the preparation and characterisation of calcium ferrite nanoparticles has been performed using solid state technique by the use of iron nitrate and calcium nitrate in equimolar quantities, which have been mixed using ethylene glycol. Influence of temperature, preparation technique, duration of calcination of granules and presence of air in laboratory atmosphere has also been studied. Method: In the current experiment, the preparation and characterisation of calcium ferrite nanoparticles has been performed using solid state technique by the use of iron nitrate and calcium nitrate in equimolar quantities, which have been mixed using ethylene glycol. Results: Initially, X-ray diffraction results showed that the optimum temperature for phase growth and the onset of single-phase calcium ferrite nanoparticles was 400 °C with an exposure time of 4 hours; infrared spectroscopy results revealed the presence of functional groups, and the type of bonds in the structure was identified. As for the scanning electron microscopy results, these revealed the presence of distinctive spherical shapes in the nanoparticles. The results of this analysis also showed that as the sintering temperature increased, the nanoparticle size increased without affecting the spherical shape. The magnetic properties of the samples were also examined; the results revealed magnetic relaxation loops for the nanoparticles at different temperatures. It was found that the coercive magnetic field was zero, and it was also found that the nanoparticles exhibited superparamagnetic properties. Novelty: Influence of temperature, preparation technique, duration of calcination of granules and presence of air in laboratory atmosphere has also been studied.